Reconstruction of copyright law to accommodate generative artificial intelligence works - Ngakan Prananta Britania (Journal of Law, Administration, and Social Science, 2026)
The development of generative Artificial Intelligence (AI) has challenged the foundations of copyright law, which has traditionally required human contribution or human authorship as a prerequisite for copyright protection. In Indonesia, Law Number 28 of 2014 on Copyright does not explicitly regulate the legal status of works generated through the use of AI, resulting in a normative gap that may encourage practices aimed at avoiding royalty obligations, as reflected in the Constitutional Court case Number 37/PUU-XXIII/2025. This study employs a normative legal research method using statutory, conceptual, and comparative approaches. The analysis is conducted through Gustav Radbruch's Theory of the Purpose of Law to examine the fulfillment of justice, legal certainty, and utility, as well as Nonet and Selznick's Responsive Law Theory to evaluate the ability of the legal system to respond to technological disruption. The findings indicate that a comparative study of regulations in the United States, the European Union, and China demonstrates that these three jurisdictions continue to uphold the principle of human creative contribution as the basis for copyright protection, albeit with varying degrees of responsiveness. The European Union adopts the most systematic approach through risk-based regulation, the United States remains adaptive through the development of judicial precedents, while China demonstrates a progressive approach by recognizing prompt engineering as a form of human creativity under certain circumstances. This study concludes that Indonesia's Copyright Law requires a paradigmatic reconstruction through the redefinition of the concept of authorship for AI-assisted and AI-generated works, the regulation of Text and Data Mining through an opt-out mechanism, the implementation of compulsory collective licensing to ensure a fairer distribution of royalties, as well as transparency and labeling obligations for works generated with the assistance of generative AI.